Praktik Mediasi Secara Elektronik dalam Perkara Perceraian di Pengadilan Agama Bantul - Zazabila Lombontari (Jurnal Hukum dan Sosial Politik, 2026)
This study aims to determine the practice of electronic mediation in divorce cases and the mediators' efforts to address obstacles affecting the implementation of electronic mediation at the Bantul Religious Court. Electronic mediation is a form of adaptation of the judicial system to developments in information technology as regulated in Supreme Court Regulation of the Republic of Indonesia Number 1 of 2016 concerning Mediation Procedures in Court and Supreme Court Regulation of the Republic of Indonesia Number 3 of 2022 concerning Electronic Mediation in Court. This study uses an empirical normative legal research method with a descriptive-analytical qualitative approach. In practice, the mediator facilitates dialogue and negotiations through electronic media such as Zoom Meeting, WhatsApp Video Call, and Google Meet to reach a peaceful agreement. Electronic mediation provides benefits in the form of easy access to justice, time efficiency, and cost reduction for the parties. However, the implementation of electronic mediation still faces several obstacles, including internet network disruptions, obstacles to the parties' use of information technology, communication barriers in virtual mediation, and low participation and good faith from the parties. To overcome these obstacles, mediators undertake various efforts, such as providing technical assistance in using the application, ensuring device and internet network readiness, establishing persuasive communication, and encouraging active participation by the parties in the mediation process. Therefore, the success of electronic mediation is determined not only by the availability of technology but also by the mediator's ability to manage the various obstacles that arise during the mediation process.